Targeting agricultural research and extension for food security and poverty alleviation: a case study of fish farming in Central Cameroon - Brummett, R.E.; Gockowski, J.; Pouomogne, V.; Muir, J. (Elsevier, 2011)
Over 5 years of participatory on-farm research, market access, profitability, farming systems productivity and economic sustainability were compared on 100 small-scale farms in Central Cameroon. Integration technology based on the use of agricultural by-products as fishpond inputs was the driver for intensification. Over all farms, fishpond productivity increased from 498 kg to 1609 kg fish/ha (2145 kg/ha/yr). During the project period, the number of active fish farmers increased from 15 to 192 (including 55 farms which participated only through information exchange). Over all farms, net returns from aquaculture increased by 5 times over pre-project levels. Productivity, intensity and profitability increased more significantly in periurban areas with good market access, compared to rural areas. Among farmers with good market access, average net income from the aquaculture enterprise rose from $118 up to $1485. Research-Extension Team (RET) support cost an average of $61,300 per year. Over 5 years, rural farmers recaptured 23% of the relevant RET investment compared to 442% by periurban farmers. Likewise, increase in production attributable to RET intervention was higher for periurban (253%) compared to rural (11.3%) fish farmers. Within 3 years of the end of extension support, rural farmers had returned to pre-project production levels, whereas periurban farms had better maintained their productivity and profitability. Findings indicate that, in areas with little or no access to markets, the number of fishponds and fish farmers can be increased and yields improved, increasing local food supplies, but sustainability in the absence of extension subsidies is questionable. To achieve either of the two principal goals for the sector, food security and/or poverty alleviation, investments need to be made in improving the availability of quality technical assistance to targeted farmers and finding means of reducing social conflict arising from perceived inequalities in the accrual of the benefits of development.